Che è «successo»? - Giulio Citroni (Quaderni di Sociologia, 2012)
Deliberative and participatory democracy is embodied in a number of techniques and methodologies for participation and deliberation which are seldom evaluated as substantial parts of policy processes. The definition of criteria for their evaluation, the development of methods and techniques for the collection and analysis of data, and the interpretation of results are far from simple. The article reviews the literature on the evaluation of deliberative and participatory practices, highlights a number of open issues concerning the feasibility of evaluation and suggests an agenda for future research.